Si3n4 ceramic wave-transparent material and preparation method thereof
Patent Information
- Application Number
- CN202610826383.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-09
- Publication Date
- 2026-08-28
AI Technical Summary
[0005]为了解决现有Si3N4陶瓷透波材料因采用毒性高的丙烯酰胺体系所导致的Si3N4料浆稳定性差、成型坯体均匀性不足以及透波性能与力学性能下降的问题,本发明提供一种Si3N4陶瓷透波材料及其制备方法
1、本发明以αSi3N4粉体为原料,配合Y2O3-Al2O3-SiO2复合烧结助剂,采用DMAA凝胶体系,通过αSi3N4粉体与复合烧结助剂质量比6~16:1的配比调控,实现低介电常数、低介电损耗与高温力学性能的协同优化。本发明中复合烧结助剂在烧结过程中形成液相促进致密化,同时控制其含量避免介电性能劣化;DMAA单体毒性远低于传统丙烯酰胺,凝胶体系固化后形成三维网络有效固定粉体颗粒,保障坯体均匀性,符合环保要求,适用于工业化批量生产。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic microwave-transparent materials technology, specifically to a Si3N4 ceramic microwave-transparent material and its preparation method. Background Technology
[0002] Currently, Si3N4 ceramics have become a core candidate material for aerospace radar radomes and high-speed aircraft wave-transparent structural components due to their high temperature resistance, high hardness, high strength, excellent thermal shock resistance, and low dielectric properties. Wave-transparent materials must simultaneously meet the requirements of low dielectric constant and low dielectric loss to ensure signal transmission efficiency, as well as sufficient mechanical strength to withstand aerodynamic loads and high-temperature thermal shock. The synergistic control of these two aspects is the key technology.
[0003] Existing molding processes for Si3N4 microwave-transparent materials mainly include dry pressing, isostatic pressing, injection molding, and gel casting. Dry pressing and isostatic pressing struggle to achieve both complex shapes and material uniformity, resulting in poor consistency in density and dielectric properties after sintering. Injection molding suffers from difficulties in debinding and organic residues, leading to increased dielectric loss. In contrast, gel casting enables the integral molding of complex shapes and is a research hotspot for Si3N4 microwave-transparent materials.
[0004] Currently, Si3N4 microwave-transparent materials are formed using acrylamide as the organic monomer, through acrylamide polymerization to create a gel network. However, acrylamide monomers are highly toxic and have poor environmental friendliness. Moreover, when using an acrylamide system, the surface of Si3N4 powder is prone to hydrolysis, making it difficult to prepare a stable slurry with high solid content and low viscosity. This results in insufficient uniformity of the molded green body, and after sintering, defects such as pores and cracks easily form inside the material, ultimately leading to a significant decrease in both mechanical properties and microwave transmission performance. Summary of the Invention
[0005] To address the problems of poor stability of Si3N4 slurry, insufficient uniformity of molded green bodies, and decreased wave transmission and mechanical properties caused by the use of highly toxic acrylamide systems in existing Si3N4 ceramic wave-transparent materials, this invention provides a Si3N4 ceramic wave-transparent material and its preparation method.
[0006] This invention uses high-purity α-Si3N4 powder as the matrix, combined with composite sintering aids, and adopts a low-toxicity DMAA monomer system to replace traditional acrylamide. By adjusting the mass ratio of α-Si3N4 powder to composite sintering aids and the content of DMAA gel system components, it is prepared through gel curing, segmented drying, degreasing and pressureless sintering, taking into account both wave transmission performance and high-temperature mechanical properties.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows.
[0008] The first objective of this invention is to provide a Si3N4 ceramic microwave-transparent material. This Si3N4 ceramic microwave-transparent material is prepared by mixing αSi3N4 powder, a composite sintering aid, DMAA gel system components, and water to prepare a Si3N4 slurry. The Si3N4 slurry is then gel-cured to obtain a wet blank, which is subsequently dried in stages, degreased, and sintered without pressure. The mass ratio of αSi3N4 powder to the composite sintering aid is 6–16:1; the amount of the DMAA gel system components added is 8%–12% of the total mass of the αSi3N4 powder, the composite sintering aid, and the DMAA gel system components. The DMAA gel system comprises DMAA monomers, crosslinking agents, dispersants, and initiators; wherein the mass of DMAA monomers accounts for 6% to 10% of the total mass of αSi3N4 powder, composite sintering aid, and DMAA gel system components; the mass of crosslinking agents accounts for 2% to 5% of the mass of DMAA monomers; the mass of dispersants accounts for 0.5% to 1.5% of the total mass of αSi3N4 powder, composite sintering aid, and DMAA gel system components; and the mass of initiators accounts for 0.1% to 0.3% of the total mass of αSi3N4 powder, composite sintering aid, and DMAA gel system components.
[0009] Preferably, the αSi3N4 powder has a particle size of 0.5μm to 2μm, an oxygen content of 0.5wt% to 1wt%, and a purity of 99% to 99.9%.
[0010] Preferably, the composite sintering aid is obtained by mixing Y2O3, Al2O3 and SiO2 in a mass ratio of 1.5 to 2.5:1:1.
[0011] The second objective of this invention is to provide a method for preparing Si3N4 ceramic microwave-transparent material, comprising the following steps: The DMAA gel system components were mixed with water, and the pH was adjusted to 8.5–10.5. α-Si3N4 powder and composite sintering aid were added to obtain a Si3N4 slurry. The solid volume fraction of the Si3N4 slurry was 50%–58%, and the viscosity was 0.8 Pa·s–1.0 Pa·s. The Si3N4 slurry was gel-cured to obtain a wet blank, which was then dried in sections to obtain a dry blank. The dry blank was degreased in sections under nitrogen protection to obtain a degreased blank. The degreased blank was then subjected to pressureless sintering under nitrogen protection, and cooled with the furnace after sintering to obtain a Si3N4 ceramic microwave-transparent material. The pressureless sintering parameters were: the first stage sintering temperature was 1200℃–1450℃, the heating rate was 5℃ / min, and the holding time was 1h–2h; the second stage sintering temperature was 1600℃–1750℃, the heating rate was 5℃ / min, and the holding time was 2h–3h.
[0012] Preferably, the parameters for the segmented drying are as follows: the temperature of the first stage of drying is 25℃~35℃, the relative humidity is 60%~80%, and the time is 12h~24h; the temperature of the second stage of drying is 60℃~80℃, and the time is 6h~12h; the temperature of the third stage of drying is 100℃~120℃, and the drying time is 4h~8h.
[0013] Preferably, the segmented degreasing method is as follows: the first stage of degreasing is carried out at 300°C, and the second stage of degreasing is carried out at 550°C.
[0014] Preferably, the crosslinking agent is N,N'-methylenebisacrylamide; the dispersant is ammonium polyacrylate or polyethylene glycol; and the initiator is an aqueous solution of ammonium persulfate, the concentration of which is 10wt% to 15wt%.
[0015] Preferably, the moisture content of the dried blank is ≤0.5%.
[0016] Preferably, the sintering temperature of the second stage is 1650℃~1700℃, and the holding time is 2h.
[0017] Preferably, the nitrogen flow rate is 0.5 L / min to 1.0 L / min.
[0018] Preferably, the αSi3N4 powder and the composite sintering aid need to be pretreated before the experiment. Specifically, the αSi3N4 powder and the composite sintering aid are passed through a 200-mesh sieve and dried at 100℃~120℃ for 2h~4h.
[0019] The beneficial effects of this invention are: 1. This invention uses αSi3N4 powder as raw material, combined with a Y2O3-Al2O3-SiO2 composite sintering aid, and employs a DMAA gel system. By controlling the mass ratio of αSi3N4 powder to the composite sintering aid at 6–16:1, it achieves synergistic optimization of low dielectric constant, low dielectric loss, and high-temperature mechanical properties. In this invention, the composite sintering aid forms a liquid phase during sintering to promote densification, while its content is controlled to avoid degradation of dielectric properties. The toxicity of DMAA monomer is far lower than that of traditional acrylamide. After the gel system solidifies, it forms a three-dimensional network that effectively fixes the powder particles, ensuring the uniformity of the green body, meeting environmental protection requirements, and is suitable for industrial mass production.
[0020] 2. The Si3N4 ceramic microwave-transparent material prepared by this invention has a relative density ≥95%, an X-band dielectric constant of 2.8~3.5, and a dielectric loss ≤5×10⁻⁶. -3 Flexural strength ≥ 600 MPa, fracture toughness ≥ 5.5 MPa·m 1 / 2 It possesses both excellent wave transmission performance and high-temperature mechanical properties. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.
[0022] Existing Si3N4 microwave-transparent materials use acrylamide as an organic monomer and form a three-dimensional gel skeleton through AM polymerization. However, AM monomers are highly toxic, carcinogenic, and environmentally unfriendly. Furthermore, Si3N4 powder is prone to surface hydrolysis in AM water-based systems, making it difficult to prepare stable slurries with high solid content and low viscosity. This results in poor uniformity of the green body, and after sintering, the material is prone to pores and cracks, leading to a significant decrease in mechanical properties and microwave transmission performance.
[0023] This invention uses a low-toxicity DMAA monomer system to replace traditional acrylamide. By selecting dispersants, adjusting pH, and optimizing solid content, a highly stable Si3N4 slurry with a solid volume fraction of 50%–58% and a viscosity of 0.8 Pa·s–1 Pa·s is prepared to ensure casting quality. A segmented drying regime is designed to avoid cracking due to the characteristics of wet blanks, and low-temperature segmented degreasing is used to thoroughly remove organic components, preventing shrinkage cracking and performance degradation of the degreased blank. Finally, the pressureless sintering process under nitrogen protection is optimized, including heating rate, holding temperature, and time. High densification is achieved by utilizing the synergistic effect of liquid phase sintering and β-Si3N4 grain growth, while simultaneously controlling the pore structure and grain morphology. This solves the problems of poor slurry stability, easy cracking of the blank, and numerous pores and cracks after sintering in existing technologies, thus achieving both microwave transmission performance and high-temperature mechanical properties.
[0024] The technical solution of the present invention will be further described below through specific embodiments. Unless otherwise specified, the methods described in the following embodiments are conventional methods; the reagents and materials described are commercially available unless otherwise specified.
[0025] Example 1 A method for preparing a Si3N4 ceramic microwave-transparent material includes the following steps: Raw materials were weighed by mass percentage as follows: 85% αSi3N4 powder, particle size 1μm, oxygen content 0.8wt%, purity 99.6%; 10% composite sintering aid, Y2O3, Al2O3 and SiO2 in a mass ratio of 2:1:1; 8% DMAA gel system components, containing 8% DMAA monomer, 2% MBAM crosslinking agent, 1% ammonium polyacrylate dispersant, 0.2% APS initiator, and the balance being deionized water.
[0026] S1. Raw material pretreatment: Pass αSi3N4 powder and composite sintering aid through a 200-mesh sieve and dry at 110℃ for 3 hours for later use.
[0027] Preparation of S2 and Si3N4 slurries: Ammonium polyacrylate dispersant was added to deionized water and stirred until dissolved. Then, DMAA monomer and MBAM crosslinking agent were added and stirred for 40 min. The pH was adjusted to 9 with ammonia water to obtain a premixed solution. The pretreated αSi3N4 powder and composite sintering aid were added to the premixed solution and ball-milled for 3 h with a ball-to-powder mass ratio of 2.5:1 to obtain a mixed powder slurry. The mixed powder slurry was degassed under a vacuum of -0.085 MPa for 20 min. APS initiator was added and stirred evenly. The solid volume fraction of the slurry was controlled to be 55% and the viscosity to be 0.8 Pa·s to obtain Si3N4 slurry.
[0028] S3, Injection molding: Inject Si3N4 slurry into the mold, gel and solidify at 60℃ for 1.5h, and demold to obtain a wet blank.
[0029] S4. Segmented drying: The wet blank is first dried at 30℃ and 70% relative humidity for 18 hours, then transferred to 60℃ for 8 hours, and finally dried at 110℃ for 6 hours to obtain a dry blank with a moisture content of 0.4%.
[0030] S5. Low-temperature degreasing: Place the dry blank in a degreasing furnace and degrease in stages under nitrogen protection: raise the temperature from room temperature to 300℃ at a rate of 1℃ / min and hold for 2 hours; raise the temperature from 300℃ to 550℃ at a rate of 0.5℃ / min and hold for 2 hours to completely remove organic components and obtain a degreased blank.
[0031] S6. Pressureless sintering: The degreased blank is subjected to two-stage heating and pressureless sintering under nitrogen protection at a flow rate of 0.8 L / min. The first stage sintering temperature is 1200℃, the heating rate is 5℃ / min, and the holding time is 1h; the second stage sintering temperature is 1680℃, the heating rate is 5℃ / min, and the holding time is 3h. After sintering, the blank is cooled with the furnace to obtain Si3N4 ceramic microwave-transparent material.
[0032] Example 2 A method for preparing a Si3N4 ceramic microwave-transparent material includes the following steps: Raw materials by mass percentage: 82% αSi3N4 powder, particle size 0.8μm, oxygen content 0.9wt%, purity 99.5%; 12% composite sintering aid, Y2O3, Al2O3 and SiO2 in a mass ratio of 2:1:1; 10% DMAA gel system components, containing 7% DMAA monomer, 3% MBAM crosslinking agent, 1.2% polyethylene glycol dispersant, 0.25% APS initiator, and the balance being deionized water.
[0033] The experimental procedure is the same as in Example 1, except that in step S6, the sintering temperature of the second stage of pressureless sintering is 1650℃ and the holding time is 3h.
[0034] Example 3 A method for preparing a Si3N4 ceramic microwave-transparent material includes the following steps: The raw materials are weighed by mass percentage as follows: 88% αSi3N4 powder, particle size 1.5μm, oxygen content 0.7wt%, purity 99.7%; 8% composite sintering aid, Y2O3, Al2O3 and SiO2 in a mass ratio of 2:1:1; 12% DMAA gel system components, containing 9% DMAA monomer, 2.5% MBAM crosslinking agent, 0.8% ammonium polyacrylate dispersant, 0.18% APS initiator, and the balance being deionized water.
[0035] The experimental procedure is the same as in Example 1, except that in step S6, the sintering temperature of the second stage of pressureless sintering is 1700℃ and the holding time is 3h.
[0036] Comparative Example 1 The raw materials are the same as in Example 1, except that the DMAA monomer is replaced with acrylamide.
[0037] The preparation steps are the same as in Example 1.
[0038] Comparative Example 2 The raw materials are the same as in Example 1.
[0039] The preparation steps are the same as in Example 1, except that the sintering temperature of the second stage of pressureless sintering in step S6 is 1550℃ and the holding time is 3h. All other steps are the same.
[0040] Comparative Example 3 The raw materials are the same as in Example 1.
[0041] The preparation steps are the same as in Example 1, except that the sintering temperature of the second stage of pressureless sintering in step S6 is 1780℃ and the holding time is 3h. All other steps are the same.
[0042] The performance of the Si3N4 ceramic microwave-transparent materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested, and the results are shown in Table 1.
[0043] Table 1. Performance test results of Si3N4 ceramic microwave-transparent materials The materials prepared in Examples 1 to 3 have a relative density of 95.5% to 96.5%, an X-band dielectric constant of 3.0 to 3.4, and a dielectric loss of 3.8 × 10⁻⁶. -3 ~4.8×10 -3Flexural strength 620MPa~670MPa, fracture toughness 5.6MPa·m 1 / 2 ~6.0MPa·m 1 / 2 All of them exhibit good mechanical properties and wave transmission performance.
[0044] Comparative Example 1 uses a traditional acrylamide system, and its performance is similar to that of the examples, but the AM monomer is highly toxic, increasing environmental costs; Comparative Example 2 has a sintering temperature of 1550℃ that is too low, with a relative density of only 92.0%, and insufficient density leads to significant deterioration in mechanical and wave transmission properties; Comparative Example 3 has a sintering temperature of 1780℃ that is too high, and abnormal grain growth increases the dielectric constant and dielectric loss, resulting in poor wave transmission performance.
[0045] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A Si3N4 ceramic microwave-transparent material, characterized in that, The Si3N4 ceramic microwave-transparent material is prepared by mixing αSi3N4 powder, composite sintering aid, DMAA gel system components and water to prepare Si3N4 slurry, gel solidifying the Si3N4 slurry to obtain a wet blank, and then preparing it by segmented drying, degreasing and pressureless sintering. The mass ratio of the αSi3N4 powder to the composite sintering aid is 6 to 16:
1. The amount of the DMAA gel system components added is 8% to 12% of the total mass of αSi3N4 powder, composite sintering aid, and DMAA gel system components; The DMAA gel system comprises DMAA monomers, crosslinking agents, dispersants, and initiators; The mass of DMAA monomer accounts for 6% to 10% of the total mass of αSi3N4 powder, composite sintering aid, and DMAA gel system components; the mass of crosslinking agent accounts for 2% to 5% of the mass of DMAA monomer; the mass of dispersant accounts for 0.5% to 1.5% of the total mass of αSi3N4 powder, composite sintering aid, and DMAA gel system components; and the mass of initiator accounts for 0.1% to 0.3% of the total mass of αSi3N4 powder, composite sintering aid, and DMAA gel system components.
2. The Si3N4 ceramic microwave-transparent material according to claim 1, characterized in that, The particle size of the αSi3N4 powder is 0.5μm to 2μm.
3. The Si3N4 ceramic microwave-transparent material according to claim 1, characterized in that, The composite sintering aid is obtained by mixing Y2O3, Al2O3 and SiO2 in a mass ratio of 1.5 to 2.5:1:
1.
4. A method for preparing the Si3N4 ceramic microwave-transparent material according to any one of claims 1 to 3, characterized in that, Includes the following steps: The DMAA gel system components were mixed with water, the pH was adjusted to 8.5–10.5, αSi3N4 powder and composite sintering aid were added, and the mixture was mixed to obtain Si3N4 slurry; the solid volume fraction of the Si3N4 slurry was 50%–58%, and the viscosity was 0.8 Pa·s–1 Pa·s. The Si3N4 slurry was gel-cured to obtain a wet preform, and the wet preform was dried in sections to obtain a dry preform. The dry blank was degreased in stages under nitrogen protection to obtain a degreased blank; the degreased blank was then subjected to pressureless sintering under nitrogen protection, and cooled with the furnace after sintering to obtain Si3N4 ceramic microwave-transparent material. The parameters for pressureless sintering are as follows: the first stage sintering temperature is 1200℃~1450℃, the heating rate is 5℃ / min, and the holding time is 1h~2h; the second stage sintering temperature is 1600℃~1750℃, the heating rate is 5℃ / min, and the holding time is 2h~3h.
5. The method for preparing Si3N4 ceramic microwave-transparent material according to claim 4, characterized in that, The parameters for the segmented drying are as follows: The first stage of drying involves a temperature of 25℃~35℃, a relative humidity of 60%~80%, and a time of 12h~24h. The second drying stage is carried out at a temperature of 60℃~80℃ for 6h~12h. The second stage of drying is carried out at a temperature of 100℃ to 120℃ for 4 to 8 hours.
6. The method for preparing Si3N4 ceramic microwave-transparent material according to claim 4, characterized in that, The segmented degreasing method is as follows: the first stage of degreasing is carried out at 300℃, and the second stage of degreasing is carried out at 550℃.
7. The method for preparing Si3N4 ceramic microwave-transparent material according to claim 4, characterized in that, The crosslinking agent is N,N'-methylenebisacrylamide; The dispersant is ammonium polyacrylate or polyethylene glycol; The initiator is an aqueous solution of ammonium persulfate, with a concentration of 10 wt% to 15 wt%.
8. The method for preparing Si3N4 ceramic microwave-transparent material according to claim 4, characterized in that, The moisture content of the dried blank is ≤0.5%.
9. The method for preparing Si3N4 ceramic microwave-transparent material according to claim 4, characterized in that, The second sintering temperature is 1650℃~1700℃, and the holding time is 2h.
10. The method for preparing Si3N4 ceramic microwave-transparent material according to claim 4, characterized in that, The nitrogen flow rate is 0.5 L / min to 1.0 L / min.